Does Exercise Influence Kynurenine/Tryptophan Metabolism and Psychological Outcomes in Persons With Age-Related Diseases? A Systematic Review. (February 2021) - Lim, Anthony; Harijanto, Christel; Vogrin, Sara; Guillemin, Gilles; Duque, Gustavo
Background: The kynurenine (KYN) pathway has been implicated in many diseases associated with inflammation and aging ("inflammaging"). Targeting the kynurenine pathway to modify disease outcomes has been trialled pharmacologically, but the evidence of non-pharmacological means (ie, exercise) remains unclear. Objective: We aim to assess the evidence of the effects of exercise on the kynurenine pathway and psychological outcomes. Methods: Under Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines, a systematic literature search was performed in MEDLINE, EMBASE, EMCARE, and the Cochrane Central Registry of Controlled Trials. The main outcomes were changes in kynurenine pathway metabolite levels and psychological outcomes. Results: Six studies were analyzed (total n = 379) with exercise demonstrating significant concomitant effects on kynurenine pathway metabolite levels and associated psychological outcomes in domains of somatization, anxiety, and depression. Conclusion: Exercise has significant concomitant effect on kynurenine pathway metabolite levels and psychological outcomes. However, clear limitations exist in determining if the changes in the kynurenine pathway can fully explain the changes in psychological outcomes, or whether different diseases and exercise interventions act as confounding factors.